Pendidikan Akal, Iman, Dan Ilmu Pengetahuan Dalam Perspektif Qs. Ali Imran Ayat 190–191 - Muhammad Saman Abdul Ghoni; Mahyuddin Barni (Yayasan Al-Afif, 2025)
This study addresses the dichotomy between rational, spiritual, and scientific dimensions in contemporary education by examining the integration of intellect (‘aql), faith (iman), and knowledge (‘ilm) in QS. Ali Imran verses 190–191. The research aims to reveal the educational values embedded in these verses and their relevance to Islamic education. Using a qualitative descriptive approach with library research, data were collected from the Qur’anic text as primary data and supported by classical and contemporary tafsir and scholarly literature. The findings show that tafakkur functions as an epistemological process to acquire knowledge through reflection on natural phenomena, while dhikr directs intellectual activity toward strengthening faith and divine consciousness. Knowledge, therefore, is not value-neutral but integrated with spiritual awareness. This study concludes that QS. Ali Imran 190–191 provides a normative framework for holistic Islamic education, promoting balanced intellectual, spiritual, and moral development, and offering an integrative paradigm for educational theory and practice in the modern era.